Minimally invasive open lumbar discectomy: An alternative to microlumbar discectomy - Devkota, UP; Lohani, S; Joshi, RM (Kathmandu University Medical Journal, 2010)
Background: Lumbar disc surgery has come a long way since its first description by Dandy in 1929. Evolving through the transdural approach and a laminectomy for the removal of a disc, it now surpasses the primal technique with essentially a minimally invasive procedure, an extradural approach without laminectomy. Objective: The objective of this study is to ascertain the effectiveness of Minimally Invasive Open Lumbar Discectomy in the treatment of lumbar disc prolapse. Materials and methods: It is a descriptive study entailing the patients with paramedian or central disc prolapse at single or two consecutive lumbosacral levels undergoing surgery at the National Institute of Neurological and Allied Sciences, Bansbari, Nepal, over a period of one and a half years. Patients who underwent either laminectomy or bilateral fenestration were excluded. Results of surgery were measured prospectively in terms of primary outcome measure (outcome at six months follow up as measured with Prolo Functional and Economic Scale) and secondary outcome measures (radicular pain relief, mobilisation, complication, and residual disc). Results: In the series of 137 consecutive patients, 120 fulfilled the criteria. 98.33 % of patients had an improvement in the radicular pain and ambulation was commenced from the first post-operative day. There were three instances of inadvertent dural tear without fascicle injury, and one instance of residual disc requiring reoperation. At 6 months, 97.5 % had good to excellent (grade 4, or 5) results reaching the premorbid states in the Prolo Functional and Economic Scale. Conclusion: The results of Minimally Invasive Open Lumbar Discectomy compare favourably with those of a microlumbar discectomy, and could therefore be an alternative to the latter in resource deprived circumstances. Key words: Disc prolapse; Minimally Invasive Open Lumbar Discectomy; Microlumbar Discectomy DOI: 10.3126/kumj.v7i3.2724 Kathmandu University Medical Journal (2009) Vol.7, No.3 Issue 27, 204-208